Sitafloxacin‐based third‐line rescue regimens for Helicobacter pylori infection in Japan. Issue 3 (March 2014) - Furuta, Takahisa; Sugimoto, Mitsushige; Kodaira, Chise; Nishino, Masafumi; Yamade, Mihoko; Uotani, Takahiro; Sahara, Shu; Ichikawa, Hitomi; Yamada, Takanori; Osawa, Satoshi; Sugimoto, Ken; Watanabe, Hiroshi; et al.
Abstracts Backgrounds Quinolone‐based regimens have been used as the rescue for eradication of Helicobacter pylori. Sitafloxacin is known to have low minimum inhibitory concentration for H. pylori. Here, we compared two sitafloxacin‐based eradication regimens as rescue for the eradication of H. pylori. Methods We attempted to eradicate H. pylori in 180 Japanese patients who had never failed in eradication of H. pylori with the triple proton pump inhibitor/amoxicillin/clarithromycin therapy (1st line) and the triple proton pump inhibitor/amoxicillin/metronidazole therapy (2nd line). They were assigned to either the triple therapy with rabeprazole 10 mg b.i.d./q.i.d., amoxicillin 500 mg q.i.d, and sitafloxacin 100 mg b.i.d. (RAS) for 1 or 2 weeks or the triple therapy with rabeprazole 10 mg b.i.d./q.i.d., metronidazole 250 mg b.i.d., and sitafloxacin 100 mg b.i.d. (RMS) for 1 or 2 weeks. Eradication was assessed via the 13C‐urea breath test and rapid urease test. Results Intention‐to‐treat and per‐protocol analyses of eradication rates were 84.1% (37/44) and 86.4% (37/43) with RAS for 1 week, 88.9% (40/45) and 90.9% (40/44) for RAS for 2 weeks, 90.9% (40/44) and 90.9% (40/44) for 1 week‐RMS and 87.2% (41/47) and 91.1% (41/45) with RMS for 2 weeks. We noted no statistical significant differences in eradication rates among four regimens. Conclusion All of the above‐described rescue regimens proved relatively equally useful in the eradication of H. pylori. Of them, RAS for 2 weeks and RMS for 1 or 2 weeks could attain the rescue eradication rates higher than 90% by per‐protocol analysis.